Ballistic testing and thermal behavior of cast double-base propellant containing BuNENA - Maraden, Ahmed Mohamed Ali; Stojan, Petr; Matyáš, Robert; Zigmund, Jan (My University, 2017)
Preparation of cast double-propellant grains depends on the ability of nitrocellulose powder to swell and coalesce into a coherent mass when treated with a suitable solvent. The cast double-base process has been developed into a highly versatile technique for manufacturing solid rocket charges. Propellants manufactured by this process provide a wide range of energies and burning rates. Successful preparation of cast double-base propellant grains has been performed using compatible casting liquid with the casting powder. BuNENA was used as an energetic plasticizer for manufacturing of casting powder. Burning rate measurements have been performed using closed bomb SV-2 to investigate the burning behavior along a wide range of operating pressure. Plateau burning had been detected in pressure range (50-70)×105 Pa for the composition included BuNENA. DTA and TGA thermal analysis were conducted to evaluate the thermal behavior of the prepared cast double-base propellants. Results from DTA were used to calculate the apparent activation energy.
Vliv plastifikátoru BuNENA na balistické a termické vlastnosti homogenních TPH
Keywords: část double- base propellant; burning rate; thermal analysis; BuNENA plasticizer; nasakované TPH; rychlost hoření; termická analýza; plastifikátor BuNENA